Improvement of the monochrome image hologram by using a random phase and increasing number of Samples (Baghdad Science Journal, 2008)
This paper present a study about effect of the random phase and expansion of the scale sampling factors to improve the monochrome image hologram and compared it with previous produced others. Matlab software is used to synthesize and reconstruction hologram.